2017
DOI: 10.1242/dev.143958
|View full text |Cite
|
Sign up to set email alerts
|

Stage- and subunit-specific functions of polycomb repressive complex 2 in bladder urothelial formation and regeneration

Abstract: Urothelium is the protective lining of the urinary tract. The mechanisms underlying urothelial formation and maintenance are largely unknown. Here, we report the stage-specific roles of PRC2 epigenetic regulators in embryonic and adult urothelial progenitors. Without Eed, the obligatory subunit of PRC2, embryonic urothelial progenitors demonstrate reduced proliferation with concomitant dysregulation of genes including Cdkn2a ( p16), Cdkn2b ( p15) and Shh. These mutants display premature differentiation of kera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 50 publications
(75 reference statements)
2
16
0
Order By: Relevance
“…To determine whether Kdm6a functions as a tumor suppressor in vivo, we crossed mice with a conditional allele of Kdm6a ( 24 ) with a urothelium-specific Cre driver, Upk2-Cre ( 26 ). The resulting Kdm6a conditional knockout (cKO) mice were viable and fertile with no apparent phenotype.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine whether Kdm6a functions as a tumor suppressor in vivo, we crossed mice with a conditional allele of Kdm6a ( 24 ) with a urothelium-specific Cre driver, Upk2-Cre ( 26 ). The resulting Kdm6a conditional knockout (cKO) mice were viable and fertile with no apparent phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…Eed is an obligatory component of PRC2. We have reported that urothelium-specific cKO of Eed completely abolishes PRC2 activity ( 26 ). We found that Cdkn1a was significantly up-regulated in the bladder urothelium of Eed cKO mice ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, exposure of human bladder urothelial carcinoma cells to UPEC in vitro induces expression of Ezh2, the methyltransferase of polycomb repressor complex 2 (PRC2) (43), which catalyzes formation of H3K27me3. We have previously reported that the PRC2-dependent H3K27me3 modification plays a critical role in the bladder urothelium during embryonic development (9). However, it's potential role in mature urothelial cells during UTIs has not been reported yet.…”
Section: Introductionmentioning
confidence: 96%
“…Nevertheless, bladder urothelium has a remarkable regenerative capacity to maintain its barrier function after injuries (8). For example, during urinary tract infections (UTIs), the quiescent urothelium becomes hyperproliferative and regenerates the superficial or umbrella cells within days to repair the damaged tissue (9)(10)(11)(12)(13). The rapid regenerative kinetics of the bladder urothelium appears to be biologically necessary for the restoration of the barrier function.…”
Section: Introductionmentioning
confidence: 99%